2011
DOI: 10.7773/cm.v37i4a.1903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal stress on survival and delay of metamorphosis in larvae of the purple sea urchin Strongylocentrotus purpuratus

Abstract: The effect of thermal stress (heat shock) on survival was evaluated for advanced larval stages and the possible effect on delay of metamorphosis in competent larvae was also evaluated in the purple sea urchin Strongylocentrotus purpuratus under laboratory conditions. Eight-arm precompetent and competent larvae were kept at 15, 19, 23, 28, and 31 ºC during 24 h to estimate their thermal tolerance and measure their survival in each treatment. Delay of metamorphosis was evaluated in competent larvae exposed to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…Overall, almost all treatment histories showed smaller sizes at death than control larvae, which indicates that any form of stress experienced either by parents or during development, and not necessarily both, has negative influences on larvae and a potential propensity to increase larval duration and postpone the point of competence, although this remains speculative. In this respect, larvae herein emulated trends already observed in other taxa Diaz-Perez & Carpizo-Ituarte, 2011). Larvae whose parents and egg masses were exposed to copper died at sizes very close to that at which they hatched, and thus probably young.…”
Section: Summary Of Findingssupporting
confidence: 79%
“…Overall, almost all treatment histories showed smaller sizes at death than control larvae, which indicates that any form of stress experienced either by parents or during development, and not necessarily both, has negative influences on larvae and a potential propensity to increase larval duration and postpone the point of competence, although this remains speculative. In this respect, larvae herein emulated trends already observed in other taxa Diaz-Perez & Carpizo-Ituarte, 2011). Larvae whose parents and egg masses were exposed to copper died at sizes very close to that at which they hatched, and thus probably young.…”
Section: Summary Of Findingssupporting
confidence: 79%
“…This type of information is very scarce for this study area and is only known for two species of sea urchins: Strongylocentrotus purpuratus (Stimpson) and Toxopneustes roseus (A. Agassiz). In precompetent and competent larvae of S. purpuratus lethal effects were produced, with 100% mortality ( Díaz-Pérez and Carpizo-Ituarte, 2011 ). Mejía-Gutiérrez et al (2019) observed that continuous exposure to a temperature of 32°C turned out to be deleterious for T. roseus with more than 90% abnormal embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Similarmente a la salinidad, algunas investigaciones han demostrado que otros factores tales como los cambios de pH y temperatura generan efectos adversos sobre la fertilización y el desarrollo temprano en equinoideos (Olaechea et al, 2006;Dupont et al, 2008;Dupont & Thorndyke, 2009, González-Delgado et al, 2014. En Paracentrotus lividus se ha demostrado efectos antagónicos sobre la fertilización y el desarrollo temprano producidos por el calentamiento del agua, que tienden a acelerar estos procesos, y la acidificación a retrasar su desarrollo (Sala & Zabala, 1996;Díaz-Pérez & Carpizo-Ituarte, 2011). Los hallazgos de esta investigación muestran que es factible utilizar rangos de salinidades entre 20 y 32 ups para el normal desarrollo de los embriones de A. stellata.…”
Section: Discussionunclassified